Pengaruh Variasi Produk Dan Iklan Di Instagram Terhadap Keputusan Pembelian Pada Brand Khansfootwear Online Store - Elan Rusnendar (LPPM Universitas Informatika dan Bisnis Indonesia, 2022)
This study aims to determine the description of Product Variations and Instagram Ads on Purchase Decisions on Khansfootwear Products. This study uses quantitative research methods with descriptive and verification approaches. The population of this research is the number of sandal buyers from the Khansfootwear Instagram account as many as 12,336 from January 2020 - June 2021, then the sample used in this study is 100 sandal buyers from the Khansfootwear Instagram account using probability sampling technique using random sampling technique. Based on the results of the study, it was found that purchasing decisions were included in the high/good category, product variations were in the high/good category and Instagram ads were in the high/good category. Based on the results of the coefficient of determination test, it was obtained that Product Variations had an effect of 48.20% on Purchase Decisions, Instagram Ads had an effect of 44.30 % on Purchase Decisions, Product Variations and Instagram Ads had an effect of 55.00% on Purchase Decisions.